2021
DOI: 10.7759/cureus.20119
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Marijuana on the Incidence and Evolution of Male Infertility: A Systematic Review

Abstract: Over the past decade, the consumption of marijuana or any other form of cannabis, whether medically, recreationally, or illegally, has been escalating worldwide. The additive effect of marijuana and the easy availability could make this increasing trend possible for imperceptible outcomes affecting one's physiology on multiple levels. The rationale of this review is to study and enumerate several effects marijuana may have on male reproductive organs, especially in men who are dealing with subfertility or infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…THC doses used in the present study reflect plasma concentrations following therapeutic (0.032μM) and low (0.32μM) to high (4.8μM) recreational cannabis use [ 20 , 100 ], as per Whan et al, (2006). Plasma concentrations of THC are moderately correlated with seminal levels, ranging from 0.87–0.97ng/mL in the semen of chronic cannabis users 10–12 hours after cannabis exposure [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…THC doses used in the present study reflect plasma concentrations following therapeutic (0.032μM) and low (0.32μM) to high (4.8μM) recreational cannabis use [ 20 , 100 ], as per Whan et al, (2006). Plasma concentrations of THC are moderately correlated with seminal levels, ranging from 0.87–0.97ng/mL in the semen of chronic cannabis users 10–12 hours after cannabis exposure [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of clear medical guidelines regarding cannabis use and male fertility is largely a result of inconclusive research. Some studies report a harmful effect of cannabis on sperm counts, morphology, motility, capacitation and the acrosomal reaction (AR) [16][17][18][19][20][21][22], while others have associated cannabis use with protection against abnormal sperm motility [16] and higher sperm counts [23]. Despite the harmful impact of cannabis on sperm [21], there is very limited research investigating the effects of paternal cannabis use on more clinically relevant outcomes, such as embryo quality following IVF [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…79 Experimental studies and epidemiological human studies have indicated that marijuana use is associated with reduced sperm concentration, total sperm count, sperm morphology, and motility. [80][81][82] However, in a metaanalysis of human studies, cannabis use was not associated with a significantly increased risk of having any abnormal semen variable. Only four studies were included in the metaanalysis and there was considerable heterogeneity between the studies.…”
Section: Use Of Marijuanamentioning
confidence: 90%
“…In males, studies have reported cannabis-associated changes in sperm morphology, reduced sperm count, and altered hormone levels, potentially contributing to fertility issues. 14 Females, on the other hand, may experience irregular menstrual cycles, potential impact on fertility, and possible effects on urinary symptoms related to cannabis use. 15 The GU system plays a vital role in our overall health and wellbeing.…”
Section: Introductionmentioning
confidence: 99%